Ecological Significance of Residues Retention for Sustainability of Agriculture in the Semi-arid Tropics - Raj Gupta; DK Benbi; IP Abrol (Journal of Agronomy Research, 2021)
In South Asia, land degradation is primarily a monsoon mediated phenomenon restricted to 2-3 rainy months. The overall strategy for land degradation neutrality should (i) favour actions that keep soils covered with residues and (ii) plant kharif (rainy season) crop before the onset of monsoons to provide soil cover. Retention of anchored residues provides surface cover, increases microbial activity, carbon sequestration, and availability of nutrients. Surface retained residues reduce root zone salinization, detoxify phytotoxic monomeric Al in acidic soils and enhance the potential for use of brackish ground water in crop production. Residues covers save irrigation water and overcome the ill effects of poor agronomic and water management practices. Early direct dry seeding in surface retained residues has the potential of making kharif season planting independent of the onset of monsoon rains in South Asia and helps reduce acreages of Kharif and Rabi fallow lands. For improving carbon content in Indian soils, perhaps the most important priority is to devise tillage and crop residue management approaches that promote in situ rain water storage and its use for growing more crops. The paper summarises how crop residues fuel and drive soil functions and related ecosystem services and plant growth.
Keywords: Crop Residue